Active electrocaloric demonstrator for direct comparison of PMN-PT bulk and multilayer samples. Issue 1 (20th June 2016) - Blumenthal, P.; Molin, C.; Gebhardt, S.; Raatz, A.
ABSTRACT: One potential use of ferroelectrics is as active material in electrocaloric cooling systems. These systems promise a more energy efficient cooling process than vapor compression, thermoelectric or other current cooling systems. Currently different design types of electrocaloric cooling devices are in the focus of research. In this paper, we present an electrocaloric cooling device demonstrator working as "Active Electrocaloric Regenerator" (AER) and employing relaxor ferroelectric elements as active material. The device design is such that it allows the integration of different material systems and regenerator designs as well as a broad variation of operational parameters.